RESPON BOBOT BADAN AKHIR DAN KARKAS AYAM BROILER TERHADAP SUBSTITUSI SEBAGIAN PAKAN KOMERSIL DENGAN TEPUNG DAUN LAMTORO (Leucaena leucocephala) FERMENTASI - Bela Putra; Aswana Aswana; Feri Irawan; Mukhlis Imam Prasetyo (Jurnal Ilmu dan Teknologi Peternakan, 2021)
One of the obstacles faced by the broiler farmer breeders is the high price of feed, which can cause low profits obtained in the broiler chicken farming businesses. An alternative is to use fermented Lamtoro (Leucaena leucocephala) leaf flour. The purpose of this study was to examine the effect of partial replacement of a commercial ration with fermented Lamtoro leaf flour. This study was carried out according to a completely randomized design with five treatments and four replications for each treatment, in which each experimental unit consisted of five-day-old chicks. The treatments were L0 (100% commercial feed), L1 (95% commercial feed + 5% fermented Lamtoro leaf flour), L2 (90% commercial feed + 10% fermented Lamtoro leaf flour), L3 (85% commercial feed + 15% fermented Lamtoro leaf flour), and L4 (80% commercial feed + 20% fermented Lamtoro leaf flour). The results showed that the substitution of the commercial rations up to the level of 20% had no significant effects (P>0.05) on all parameters tested (final body weight, carcass weight, carcass percentage, and percentage of chest, thigh, or back). From this study, it can be concluded that fermented Lamtoro leaf flour can replace the use of the commercial ration of broiler up to 20%.